LAND ROADS IN MADRE DE DIOS: SOCIAL AND ENVIRONMENTAL TRANSFORMATIONS - CASTILLO-HURTADO, Jorge (2024)
The original peoples of Madre de Dios have occupied this territory for more than 5,000 years. Seven centuries ago a situation of relative autonomy passed when the Incas arrived through the first land routes that allowed access to what is currently the department of Madre de Dios. In the republican period and especially in the 20th century, definitive routes of penetration were opened that dramatically changed the social and environmental panorama. The study is descriptive, mixed approach with qualitative predominance, longitudinal design, applying the documentary review technique and qualitative techniques complemented with quantitative data and information. In the first decade of the 21st century, the construction of the Southern Interoceanic Highway was completed, which section III crosses Madre de Dios. The consequent social and environmental impacts, resulting from these different moments and visions of development, have been severe and they are evaluated in this study.